2016
DOI: 10.1016/j.enpol.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact analysis of natural gas development and the policy implications

Abstract: In the US, the shale gas revolution ensured that the development costs of unconventional natural gas plummeted to the levels of $2-$3/Mcf. This success has motivated the development of shale gas in other regions, including Australia and Europe. This study, focussing primarily on aspects of economic impact analysis, estimates the development costs of shale gas extraction in both Australia and Europe, based on both direct and fiscal costs, and also suggests policy initiatives.The increasing liquefied natural gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…As the traditional OLS regression method needs to meet a variety of assumptions prior to running, the random disturbance term should have a mean of zero and be identically distributed if the error term meets the normal distribution condition. In the actual economic situation, however, it is found that most economic indicator data does not meet the above assumptions [43]. Quantile regression can better observe the overall distribution of data without data processing, making up for some of the defects of OLS regression [44].…”
Section: Panel Quantile Regressionmentioning
confidence: 99%
“…As the traditional OLS regression method needs to meet a variety of assumptions prior to running, the random disturbance term should have a mean of zero and be identically distributed if the error term meets the normal distribution condition. In the actual economic situation, however, it is found that most economic indicator data does not meet the above assumptions [43]. Quantile regression can better observe the overall distribution of data without data processing, making up for some of the defects of OLS regression [44].…”
Section: Panel Quantile Regressionmentioning
confidence: 99%
“…We have an awareness that both scholars and the public think planning processes and Silva et al 2016]). Williams et al (2017) report scepticism amongst their focus group participants about the purported economic benefits (e.g., from job creation in the gas sector, taxes collected, expansion of ancillary industries to support SGD in areas with development), but economists have yet to assess, in the peer-reviewed literature, the UK Government and industry claims (e.g., House of Lords 2014).…”
Section: Synthesis and Future Directionsmentioning
confidence: 99%
“…It seems that a real opportunity to significantly reduce the dependence of EU economy on the supply of pipeline gas from non-EU countries (mainly from Russia, Norway, Algeria and Libya) is the development of infrastructure investments related to LNG. Available information on lessons learned from the exploitation of unconventional resources in the EU leads to a conclusion that in most cases they were unsuccessful [12]. According to information provided by the European Commission, it is estimated that in the period 2017-2023 the global LNG turnover will increase by more than 100 bcm, from 391 to 505 bcm [13].…”
Section: Developments In the Eu's Natural Gas Market Role Of Lng Supplymentioning
confidence: 99%